The role of p16 and DAPK genes in cell cycle control and in the pathways of vulvar carcinogenesis - Fialho, Susana Cristina Aidé Viviani; Vai, Isabel Cristina C.; Almeida, Gutemberg; Lattario, Fernanda; Carvalho, Maria da Gloria C. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Vulvar cancer is the fourth commonest kind of cancer in women and it represents 4.8% of cancers in the lower genital tract squamous cell carcinoma is responsible for 80-90% of all vulvar cancers. Squamous cell carcinoma and it’s premalignant lesions seem to develop in two distinct pathways, based on etiological and histopathological characteristics, thus forming a heterogeneous etiology. Whereas one of the pathways is related to HPV infection, the other is related to epithelial disorders such as: lichen sclerousus and epithelial hyperplasia. HPV is an important contributing factor of neoplasia in the lower genital tract. It is found in 90% of cervical cancers and in 30-40 % of vulvar cancers. The most prevalent kind is 16, followed by 18, 45, 31, and 33. The study of genetic and epigenetic alterations by means of methylation and genic immunoexpression has demonstrated great versatility to the monitoring of patients with cancer, which boosts researches of diagnostic and therapeutic methods for cancer. This update intends to demonstrate the role of pl6 and DAPK genes as well as the recent researches regarding the expression of these genes in the pathways of vulvar carcinogenesis.